Correlation between local structure variations and critical temperature of (Bi1.6Pb0.4Sr2Ca2Cu3O10+δ)1-x(TiO2)x superconductor. Issue 7 (1st April 2023) - Pham, An T.; Vu, Linh H.; Tran, Dzung T.; Thien, Nguyen Duy; Klysubun, Wantana; Miyanaga, T.; Man, Nguyen K.; Duong, Nhan T.T.; Long, Nguyen Thanh; Pham, Phong V.; Binh, Nguyen Thanh; Tran, Duc H.
Abstract: TiO2 doping content affects the critical temperature ( T c ) and the variations of local structure on Bi1.6 Pb0.4 Sr2 Ca2 Cu3 O10+δ . The (Bi1.6 Pb0.4 Sr2 Ca2 Cu3 O10+δ )1-x (TiO2 )x samples were fabricated with the solid-state reaction process, where x = 0, 0.002, 0.004, 0.006, 0.008, and 0.01. The T c values of the samples were obtained by measuring resistivity versus temperature, indicating that T c gradually decreased with increasing doping content ( x ). To explain the obtained degradation of T c, carrier properties, role of interlayer coupling, and local structure were systematically investigated using Azlamozov–Larkin theory and its Lawrence–Doniach modification for strong anisotropic superconductors. The calculation of excess conductivity at the mean field region showed that the c-axis coherence length ( ξ c ) and the effective inter-layering spacing ( d ) increased with increasing doping content. X-ray diffraction patterns also showed that the bond distances increased with increasing TiO2 content. The copper valence ( V ) and carrier concentration ( p ) of the samples were determined by analyzing the Cu L2, 3 -edge X-ray absorption near edge structure spectra. The values of V and p showed the same trend of decreasing with increasing x . A close correlation between the changes in local structure parameters and degradation of T c of (Bi1.6 Pb0.4 Sr2 Ca2 Cu3 O10+δ )1-x (TiO2 )x was then probably concluded.